Mechanisms of Short- and Long-Latency Sensory Suppression: Magnetoencephalography Study. (15th March 2023) - Takeuchi, Nobuyuki; Fujita, Kohei; Taniguchi, Tomoya; Kinukawa, Tomoaki; Sugiyama, Shunsuke; Kanemoto, Kousuke; Nishihara, Makoto; Inui, Koji
Highlights: Interaction between short- and long-latency suppression was studied. Prepulse suppressed following test responses. Suppression was unchanged when the prepulse-evoked response was suppressed. The short- and long-latency suppression were additive. Findings support hypothesis that suppression depends on a specific inhibitory circuit. Abstract: Prepulse inhibition (PPI) is sensory suppression whose mechanism (i.e., whether PPI originates from specific inhibitory mechanisms) remains unclear. In this study, we applied the combination of short-latency PPI and long-latency paired pulse suppression in 17 healthy subjects using magnetoencephalography to investigate the mechanisms of sensory suppression. Repeats of a 25-ms pure tone without a blank at 800 Hz and 70 dB were used for a total duration of 1600 ms. To elicit change-related cortical responses, the sound pressure of two consecutive tones in this series at 1300 ms was increased to 80 dB (Test). For the conditioning stimuli, the sound pressure was increased to 73 dB at 1250 ms (Pre 1) and 80 dB at 700 ms (Pre 2). Six stimuli were randomly presented as follows: (1) Test alone, (2) Pre 1 alone, (3) Pre 1 + Test, (4) Pre 2 + Test, (5) Pre 2 + Pre 1, and (6) Pre 2 + Pre 1 + Test. The inhibitory effects of the conditioning stimuli were evaluated using N100m/P200m components. The results showed that both Pre 1 and Pre 2 significantly suppressed the Test response. Moreover, the inhibitory effects of Pre 1 and Pre 2 were additive. However, when both prepulses were present, Pre 2 significantly suppressed the Pre 1 response, suggesting that the Pre 1 response amplitude was not a determining factor for the degree of suppression. These results suggested that the suppression originated from a specific inhibitory circuit independent of the excitatory pathway.